Die zeitliche Änderung der Wasserbindung im Boden unter verschiedenen Vegetationsformationen der Höhenstufen eines tropischen Hochgebirges (Sierra Nevada de Sta Marta / Kolumbien) - Hermann, Reimer (ERDKUNDE, 1971)
From August 1967 to March 1968 soil moisture tension was measured under different plant formations in a profile from the dry coastal fringe of the northwestern Sierra Nevada de Sta. Marta/Colombia up to the paramo (3600 m). The results showed that, under the paramo vegetation of the northwestern Sierra Nevada, there was a marked period with soil moisture tension pF 2,5-3,6, whereas under tropical ombrophilous cloud forest, the plant formation below the paramo, pF 2,5 was never surpassed. The unexpected dryer period under paramo vegetation may be explained by certain climatic and hydropedological situations. Under tropical ombrophilous montane forest in the dry season there occurred a period with a high soil moisture tension of pF 2,5-3,6. But under all three plant formations the period with < pF 2,5 (mostly free gravitational water) was predominant. The plant formation below these, a tropical evergreen seasonal submontane forest, suffers high soil moisture tensions of > pF 4,2 (conventionally permanent wilting point) in the dry season. Moving downward from tropical semi-deciduous forest to drought-deciduous lowland forest and finally to succulent drought-deciduous shrublands the period with > pF 4,2 gets increasingly longer. Even in the rainy season soil moisture tensions above pF 4,2 occurred, extending from over a few days to one month. Under tropical alluvial forest salts are enriched in the root zone by capillary supported water. If the capillary fringe reaches the surface the salt concentrates in the upper soil allowing only life for a halophytic shrubland. The results are explained by means of isopleths of soil moisture tension (pF) together with a profile of plant formations by abbreviated isopleths. A short introduction to the idea of soil moisture potential and to the climatic conditions introduce the paper.